Literary theory and its role in modern and contemporary criticism: A critical approach - Ibrahim, Abdullah Mahmod; Almazaidah, Ismail Suliman; Allawzi, Areej (Research Journal in Advanced Humanities, 2024)
This research aims to identify the relationship between the concepts of "literary theory" and "literary criticism"; as a crisis was formed in reaching an agreement between the critics on defining the concept of these terms. Thus, the research seeks to identify these two terms and examine their implications in the modern literary lesson. The research takes an analytical and investigative approach based on how to use terms, understand them and apply them in research writing. The research has found that there is a discrepancy in the use of terms and their understanding and invocation in research writing. These terms came to us from Europe, which took them from the Greek and Latin cultures. The research concludes that there is a difference between critics and writers during the literary study about basic concepts, which requires them to go through them by definition, commentary, and deduction, such as the concept of literature itself, creativity, reception, criticism, literary history, literary schools, and others.